2019
DOI: 10.1530/joe-18-0505
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II: an inflammatory cytokine

Abstract: Urotensin II (UII) is a polypeptide molecule with neurohormone-like activity. It has been confirmed that UII is widely distributed in numerous organs of different animal species from fish to mammals, including humans. The UII receptor is orphan G-protein-coupled receptor 14, also known as UT. The tissue distribution of UII and UT is highly consistent, and their expression may be regulated by autocrine and paracrine mechanisms. In the body, UII has many physiological and pathophysiological activities, such as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…Cilia defects can trigger inflammation in the kidney and in the brain [34,35]. Moreover, Urotensin II signaling induces inflammation in many contexts [36], raising the interesting possibility that increased URP signaling from CSF-cNs could drive neuroinflammation in the rpgrip1l ∆/∆ zebrafish scoliosis model.…”
Section: Discussionmentioning
confidence: 99%
“…Cilia defects can trigger inflammation in the kidney and in the brain [34,35]. Moreover, Urotensin II signaling induces inflammation in many contexts [36], raising the interesting possibility that increased URP signaling from CSF-cNs could drive neuroinflammation in the rpgrip1l ∆/∆ zebrafish scoliosis model.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, U-II plays a key role in the onset and development of inflammatory diseases. 12 Previous studies have confirmed that high levels of U-II are found in the plaques of patients with atherosclerosis. 10,27 Proinflammatory cytokines such as interleukin (IL)-6, IL-1β, and interferon (IFN)-γ in atherosclerotic plaques, which are secreted by macrophages and lymphocytes, upregulate the expression of U-II, and the specific receptor UT which accelerates the formation of atherosclerotic plaques with autocrine/paracrine effects.…”
Section: Discussionmentioning
confidence: 86%
“…11 Moreover, U-II acts as an inflammatory cytokine, which may unify the molecular basis of the innate immune and inflammatory response. 12 Elevated plasma U-II levels were detected in adults with atherosclerosis, 10 hypertension, 13,14 and congestive heart failure, 15 although other studies reported inconsistent results. 16,17 In children, on the other hand, little information is available on U-II levels at an early stage of life.…”
mentioning
confidence: 99%
“…UT is broadly expressed in the central nervous, cardiovascular, and renal systems 10 . U‐II/UT signaling participates in various biological processes, such as cell proliferation, profibrotic activities, neurosecretory effects, insulin resistance, as well as carcinogenic and pro‐inflammatory effects 11 . Numerous studies have demonstrated that increased expression levels of U‐II and UT are implicated in various disorders, including essential hypertension, atherosclerosis, heart failure, diabetes mellitus, and renal diseases 12 .…”
Section: Introductionmentioning
confidence: 99%